Allele-specific PCR with fluorescently labeled probes: criteria for selecting primers for genotyping - V. A. Devyatkin; A. A. Shklyar; A. Zh. Fursova; Yu. V. Rumyantseva; O. S. Kozhevnikova (Вавиловский журнал генетики и селекции)
Single-nucleotide polymorphisms (SNPs) can serve as reliable markers in genetic engineering, selection, screening examinations, and other fields of science, medicine, and manufacturing. Whole-genome sequencing and genotyping by sequencing can detect SNPs with high specificity and identify novel variants. Nonetheless, in situations where the interest of researchers is individual specific loci, these methods become redundant, and their cost, the proportion of false positive and false negative results, and labor costs for sample preparation and analysis do not justify their use. Accordingly, accurate and rapid methods for genotyping individual alleles are still in demand, especially for verification of candidate polymorphisms in analyses of association with a given phenotype. One of these techniques is genotyping using TaqMan allele-specific probes (TaqMan dual labeled probes). The method consists of real-time PCR with a pair of primers and two oligonucleotide probes that are complementary to a sequence near a given locus in such a way that one probe is complementary to the wild-type allele, and the other to a mutant one. Advantages of this approach are its specificity, sensitivity, low cost, and quick results. It makes it possible to distinguish alleles in a genome with high accuracy without additional manipulations with DNA samples or PCR products; hence the popularity of this method in genetic association studies in molecular genetics and medicine. Due to advancements in technologies for the synthesis of oligonucleotides and improvements in techniques for designing primers and probes, we can expect expansion of the possibilities of this approach in terms of the diagnosis of hereditary diseases. In this article, we discuss in detail basic principles of the method, the processes that influence the result of genotyping, criteria for selecting optimal primers and probes, and the use of locked nucleic acid modifications in oligonucleotides as well as provide a protocol for the selection of primers and probes and for PCR by means of rs11121704 as an example. We hope that the presented protocol will allow research groups to independently design their own effective assays for testing for polymorphisms of interest.